Short, multi-modal, pre-commencement transition programs for a diverse STEM cohort. - Larsen, Amy; Cox, Sarah; Bridge, Christopher; Horvath, Deanna; Emmerling, Michael; Abrahams, Carmel (Journal of University Teaching and Learning Practice, 2021)
A ‘quantum leap’ (Kift, 2015) in our understanding of the transition to university studies has brought about a reimagining of the role of transition programs from attempting to remediate deficiencies in ‘underprepared’ students, to instead using engagement with the curriculum to instil success-oriented behaviours and attitudes in them. In particular commencers from non-traditional backgrounds are confronted by greater sociocultural incongruities when starting higher education (Devlin, 2013), and face greater challenges in developing their new student identity. While affective change of this kind may necessarily be long-term in nature, semester or year-long ‘foundation’ or ‘bridging’ programs create barriers themselves in terms of time, cost, and stigma. This study provides evidence that significant results can be achieved with short, accessible, manageable, pre-commencement transition programs, that are situated in the curriculum, but also focussed on nurturing those behaviours and attitudes in at-risk students that are associated with greater likelihood of success and retention.